2019
DOI: 10.1038/s41536-019-0079-2
|View full text |Cite
|
Sign up to set email alerts
|

Vegfc/d-dependent regulation of the lymphatic vasculature during cardiac regeneration is influenced by injury context

Abstract: The lymphatic vasculature mediates essential physiological functions including fluid homeostasis, lipid and hormone transport, and immune cell trafficking. Recent studies have suggested that promoting lymphangiogenesis enhances cardiac repair following injury, but it is unknown whether lymphangiogenesis is required for cardiac regeneration. Here, we describe the anatomical distribution, regulation, and function of the cardiac lymphatic network in a highly regenerative zebrafish model system using transgenic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 65 publications
4
43
0
Order By: Relevance
“…We cannot rule out a direct effect on elevating the immune response with blockade of Vegfc-signal, but the resulting shift has a potent negative effect on the continuing regenerative environment of the tissue, while not directly effecting cardiomyocyte proliferation, epicardial activation, coronary vessel revascularization or heart structure and morphology (Figure 6). Consistent with our studies using sFlt4, recently it has been reported that a vegfd -mutation in a vegfc -hypermorphic background can also limit the extension of the cardiac lymphatic vessels down the ventricle while not affecting coronary vessels (Vivien et al, 2019). Further, almost half of the vegfc/d mutant zebrafish surviving to adulthood fail to complete regeneration by 180dpc (Vivien et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…We cannot rule out a direct effect on elevating the immune response with blockade of Vegfc-signal, but the resulting shift has a potent negative effect on the continuing regenerative environment of the tissue, while not directly effecting cardiomyocyte proliferation, epicardial activation, coronary vessel revascularization or heart structure and morphology (Figure 6). Consistent with our studies using sFlt4, recently it has been reported that a vegfd -mutation in a vegfc -hypermorphic background can also limit the extension of the cardiac lymphatic vessels down the ventricle while not affecting coronary vessels (Vivien et al, 2019). Further, almost half of the vegfc/d mutant zebrafish surviving to adulthood fail to complete regeneration by 180dpc (Vivien et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…The formation of the new lymphatic vessels and structures seems to follow the demand for fluid drainage from the ventricular tissue, which increases following myocardial damage. Thus, lymphatic vessels in the heart create an environment favorable to scar resolution and regeneration (which is consistent with a recent study by Vivien et al, 2019).…”
supporting
confidence: 91%
“…In mouse embryos, venous derived lymphatics were shown to give rise to the vessels paralleling the coronaries, while non-venous, Tie2-negative yolk sac derived progenitors (Klotz et al, 2015) contribute to the formation of PROX1+ LECs in the developing heart. Recently, three independent studies (Gancz et al, 2019b;Harrison et al, 2019;Vivien et al, 2019) described the development of cardiac lymphatics in zebrafish as well as their role during cardiac regeneration. Interestingly, in addition to conventional lymphatic vessels spanning the cardiac ventricle, Gancz et al (2019b) reported the presence of isolated prox1+, lyve1b+, mrc1+ and flt4+ LEC clusters in the zebrafish heart that developed initially into single capillaries, and later on connected to the existing lymphatic plexus.…”
Section: The Origins Of Lymphatics Endothelial Cellsmentioning
confidence: 99%